Functioning in chronic pain: a call for a global definition - Freynhagen, Rainer; Fullen, Brona M.; Reneman, Michiel F.; Treede, Rolf-Detlef (Pain, 2024)
An abstract is unavailable.
Gesehen am 20.11.2024